P03 Management of ovarian cysts in premenopausal women with tamoxifen. (1st November 2019) - Goeminne, A; Maggen, C; Timmerman, D; Neven, P
Abstract : Introduction/Background: In this retrospective study, we investigated the ovarian function of 69 premenopausal patients with hormone-receptor positive, human epidermal growth factor receptor 2 (HER2) negative breast cancer receiving tamoxifen with a focus on the management and survival of patients with ovarian cyst formation. Methodology: 69 premenopausal women treated with tamoxifen for early primary HER2- negative breast cancer - referred to the gynaecology ultrasound department of the university hospitals of Leuven between 2003 and 2018 - were selected. Patients that received chemotherapy, adjuvant radiotherapy or ovarian suppression were excluded. Oncological data, gynaecological ultrasound reports, details on menstruation pattern during tamoxifen and hormonal blood tests were obtained from patient records. Results: In total, 31 patients developed a cyst during tamoxifen treatment. Median age at diagnosis of breast cancer was 47 years (37–53) and younger patients were more likely to develop ovarian cysts (p<0.002). Median interval between initiation of tamoxifen and detection of ovarian cysts was 10 months (1–59). Median size of ovarian cysts was 47 mm (30–96). Most patients (20/31) were followed conservatively, with spontaneous regression of the cysts. In 4/31 patients regression occurred after interruption of tamoxifen or additional ovarian suppression. Surgery was performed in 7/31 patients for large symptomatic cysts or torsion. Bleeding pattern changed in 55 out of 68 of the patients (one patient was excluded because of hysterectomy), most frequently oligomenorrhea or amenorrhea. 13/49 available records of the patients had high oestradiol levels (>400 pg/ml) while treated with tamoxifen. Survival of all patients was excellent; with a median follow-up of 73 months no events occurred. Conclusion: We reported that the administration of tamoxifen in premenopausal women is associated with ovarian cyst formation and high estradiol levels. Ovarian cysts mostly can be managed conservatively. In this series, the impact of tamoxifen on ovarian function does not appear to affect survival. Disclosure: Nothing to disclose.